Doprowadź do najprostszej postaci i oblicz wartości liczbowe :)


a) y=-1½
-4²-1(y+1)-2y²-3×(-2)=
b) a=-2
-5a³-3(a²+5a)-6(a³+4a) =
c) x=1,5 y=0,5
4x(2x-y)-5(x²-y)+3x=
d) b=¼ c=(-¼)
2b(2b-c)-4c(2b+c)+3c²=
e) x=1½
-2(½x²-3x)-(-2x²+1)-x=

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-01T17:00:38+01:00
A) y=-1½
-4²-1(y+1)-2y²-3×(-2)=-4²-y-1-2y²+6x=8-1,5-1-2*9/4+6x=5,5-4,5=1
b) a=-2
-5a³-3(a²+5a)-6(a³+4a)=-5a³-3a²-15a³-6a³-24a=20a³-3a²-24a=-160-12-48=100
c) x=1,5 y=0,5
4x(2x-y)-5(x²-y)+3x=8x²-4xy-5x²+5y+3x=3x²-4xy+5y+3x=6,75-3+2,5+4,5=10,75
d) b=¼ c=(-¼)
2b(2b-c)-4c(2b+c)+3c²=4b²-2bc-8bc-4c²+3c²=4b²-10bc-c²=0,25+0,625-0,0625=0,8125
e) x=1½
-2(½x²-3x)-(-2x²+1)-x= -x²+6x+2x²-1=x²+6x-1=2,25+9-1=10,25